Peningkatan Mutu Kakao Melalui Percepatan Lama Fermentasi dengan Penggunaan Pektinase Aspergillus niger dan Ion Kalsium - Anggraini, Novia; Erawati, Christina Mumpuni; Putra, Sulistyo Emantoko Dwi (JURNAL AGROTEKNOLOGI, 2024)
Indonesia is the third largest producer of cocoa beans (Theobroma cacao L.) in the world, but the quality of Indonesian cocoa beans is considered as low. Fermentation is one of the factors that affect the quality of cocoa beans. Fermentation of cocoa beans is a spontaneous fermentation and takes about 5-7 days (for bulk cacao). The objective of this study was to determine the potential of adding pectinase from Aspergillus niger and calcium ions in accelerating fermentation time and the quality of cocoa beans produced. The independent variable in this study was the concentration of calcium ions as an enzyme activator. The concentration of calcium ions and pectinase are applied to cocoa fermentation. The observations made were reducing sugar content, total sugar content, protein content, lactic acid bacteria and acetic acid bacteria levels. Parametric data will be analysed by T-test independent with a confidence level of α=0.05. The results showed that added 4.5 units of pectinase and 100 mM calcium ions have significant in reduce the total sugar compared with control due to enzimatic activity. Therefore, the addition of pectinase enzymes from Aspergillus niger and calcium ions have a potential to accelerate the fermentation time and the fermented cocoa beans that have been carried out have met the quality standards of SNI 2828:2008 and included in I – B group of forastero cocoa. This potential needs to be tested further with a larger fermentation volume, for example above 40 kg, to achieve the optimal temperature for the formation of flavor precursors. Keywords: cocoa bean, ion calcium, pectinase, quality